Case Report: TEMPI syndrome: Report of three cases and treatment follow-up - Xu, Zhuo-Fan; Ruan, Jing; Chang, Long; Wu, Sijin; Lin, Jinkai; Wang, Wei; Cao, XinXin; Zhang, Lu; Li, Jian; Zhou, Daobin; Zhang, Wei (Frontiers in Oncology, 2022)
The TEMPI syndrome is a novel and rare disease with five distinct clinical features: Telangiectasis, Erythrocytosis, Monoclonal gammopathy, Perinephric fluids collection, and Intrapulmonary shunting. Here, we report three cases of TEMPI syndrome and their treatment response. The three patients were presented to our department with polycythemia, abdominal distension, and dyspnea. On admission, all patients manifested telangiectasis, erythrocytosis, monoclonal gammopathy, and intrapulmonary shunting. Patient 1 and 2 manifested perinephric fluids collection. In addition, all patients had skin pigmentation, patient 1 and 2 had polyserosal effusion, two symptoms that had not been associated with TEMPI syndrome before. The three patients showed various response to plasma cell-directed therapy. We demonstrated their treatment response by measuring erythropoietin, hemoglobin, and M protein levels throughout therapy. This report suggested that TEMPI syndrome is a rare yet treatable disease. The diagnosis and treatment of it remain challenging.